2019
DOI: 10.3166/phyto-2019-0125
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenolic Content, Anti-inflammatory, Analgesic, and Antipyretic Activities of Some Extracts ofInula viscosa(L.) from Algeria

Abstract: Inula viscosa (L.) is a medicinal plant that has been used for a long time for its many therapeutic properties, especially to treat pain and inflammation. The aim of this study was to evaluate the anti-inflammatory, analgesic, and antipyretic activities of methanolic extracts and decoctions of Inula viscosa leaves and flowers. The phenol content of the extracts was determined by spectrophotometric methods. The extracts were administered orally (400, 600, and 800 mg/kg) to mice and/or rats in the study of antii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In the study of Ouahchia et al [ 36 ], D. viscosa was reported to possess analgesic activity with 93.39% of writhing inhibition at a dose of 800 mg/kg. Additionally, in another study conducted by Martin et al [ 37 ], D. viscosa proved its analgesic activity.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Ouahchia et al [ 36 ], D. viscosa was reported to possess analgesic activity with 93.39% of writhing inhibition at a dose of 800 mg/kg. Additionally, in another study conducted by Martin et al [ 37 ], D. viscosa proved its analgesic activity.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum inhibition for writhing was observed with a dose of 800 mg/kg of the ethanolic extract obtained from leaves (93.39%). 92 The conclusions of the last studies are backed by the findings of Side Larbi et al (2016) who investigated the effect of both the methanol extract and essential oil on central analgesia in rats. The study revealed that both samples had a significant central analgesia by increasing the latency time in the tail immersion test, with a clear dose-dependent relationship in the induced analgesic effect.…”
Section: Resultsmentioning
confidence: 98%
“…However, the cytoprotection provided by CAB-DE is in part correlated to its richness in phenolic compounds which are also known for their antioxidant and anti-inflammatory properties. 54,55 Moreover, tannins have several physiological activities such as blocking the inflammatory mediator synthesis, like prostaglandins and leukotrienes. 56 The study of Pierre et al 57 has shown that condensed tannins provide the protection and integrity of intestinal physiology; they stimulate mucus secretion by goblet cells, minimize inflammatory reaction, and preserve intestinal profile.…”
Section: Discussionmentioning
confidence: 99%